POLA PERKEMBANGAN KOTA JAMBI TAHUN 2000-2020 - Fitrah Andika Riyadhno; Ahyuni Ahyuni (JURNAL BUANA, 2022)
City development is a function of time, to find outdevelopment in a city that must compare the physical condition of the cityover two time periods. One of the cities that will develop issuch as Jambi City with a population growth rate of 11.9% per yearwith a population density in Jambi City which is 2,944 people/km². urgeand the need for land is increasing, while the available landlimited, it is necessary to analyze the pattern of land use change in Jambi City tofind out how the shape of the development pattern of Jambi City every year.The methods used in this study are overlapping and spatial metricsused to determine changes in the built up area in the city of Jambi in2000-2020 and spatial patterns of land use in Jambi City. Results obtainedincreased by 3233.75464 ha with the development spreading fromthe middle of the city to the outskirts of the city, the results of the metric calculation showthe direction of the development pattern to a compact city with the existence of a built areamore and more round and round.